Antimicrobial photodynamic therapy using indocyanine green as a photosensitizer in treatment of chronic periodontitis: A clinico-microbial study - Kunal S Sethi; Chetan P Raut (Wolters Kluwer Medknow Publications, 2019)
Background: Photodynamic therapy (PDT) has gained much attention in recent years in the treatment of periodontitis. Number of photosensitizer have been developed and has been used in various clinical studies. However, the use of recently developed photosensitizer has been limited. Aim: The present study aims at comparing and evaluating the effects of photodynamic therapy using Indocyanine green in the treatment of chronic periodontitis. Materials and methods: In present randomized clinical trial, 30 subjects were equally divided into two groups i.e. test group (SRP + Photodynamic therapy) & control group (SRP). Clinical parameters evaluated at baseline and 3 month follow up were, Plaque index, Sulcus Bleeding Index, Probing Pocket Depth, Clinical Attachment Level, Gingival Recession. Microbiological analysis of plaque sample was also done to check for anaerobic mixed flora. Results: Significant reduction was seen in all the clinical parameters in the test group. Anaerobic culture of plaque samples of test group also revealed significant reduction of microorganisms in comparison with control group. Conclusion: Indocyanine Green can act as an alternative to other photosensitizers in photodynamic therapy as an adjunct to SRP in the treatment of chronic periodontitis.